International Conference on Social Development and Social Work Education - Ibrahim Rajah (International Institute of Islamic Thought, 1992)
The Twenty-Sixth Congress of the International Association of Schools of Social Work (IASSW) and the Seventh International Conference of the Inter-University Consortium for International Social Development (IUCISD) was held during 13-19 July 1992, in Washington, DC. These biennial international conferences are held simultaneously in the same location to encourage interested social work educators to participate in the activities of both conferences. IASSW represents the interests of almost two thousand schools of social work and training institutes worldwide. The theme of the 1992 conference was "Realities of Global Interdependence: Challenges to Social Work Education." Papers presented spanned the wide range of interests of social work educators, from practice theory formulations to curriculum development to indigenous case materials. They also dealt with many diverse fields of social work practice, for example, from family and child welfare to rural and urban community development. Papers also dealt with clinical practice interests, polity, planning, and social development issues. IUCISD is a younger multidisciplinary organization of social work educators and other allied professionals with an interest in the broader area of international social development. The theme of the IUCISD 1992 conference was “Strategies of Social Development for Improving the Human Condition.” Papers presented covered diverse topics, including social welfare provisions in Eastern Europe and countries of the former Soviet Union, peace and development, sustainable agriculture, refugees, social development skills, social development and indigenous populations, social development and aging populations, social development and children, and many others ...